Prospective One-Year Follow-Up of Sensory Processing in Phelan-McDermid Syndrome - Sergio Serrada-Tejeda; Patricia Sánchez-H; Rosa M. Martínez-Piédrola; Nuria Máximo-Bocanegra; Nuria Trugeda-Pedrajo; M.ª Pilar Rodríguez-Pérez; Gemma Fernández-Gómez; Marta Pérez- (MDPI AG, 2023)
Background: Phelan-McDermid syndrome (PMS) is caused by the loss (deletion) of a small portion of chromosome 22 in a region designated q13.3 (22q13.3 deletion). PMS is one of the most common genetic forms of autism spectrum disorder (ASD) in which sensory reactivity difficulties have been described on limited occasions. Methods: The objective of this study is to identify whether changes in sensory reactivity skills occur after one year of follow-up in a group of 44 participants diagnosed with PMS. All participants completed the Short Sensory Profile (SSP). Two-factor ANOVA tests were performed with repeated measures for the study of the evolution of the scores. Results: Participants with PMS showed significant changes after one year of follow-up in sensory reactivity skills associated with tactile hyperreactivity (p = 0.003). The rest of the study variables did not show significant differences compared to the baseline assessment, showing definite differences associated with patterns of hypo-responsiveness and sensory seeking, low/weak energy, and difficulties in auditory filtering. Conclusions: Understanding the evolution of sensory reactivity skills can facilitate the adjustment to behavioral changes in people with PMS and design-targeted interventions to address sensory reactivity challenges.